Application of the School Field Introduction Model to Strengthen the Competency of Biology Teacher Candidates at SMA NW Mataram: Penerapan Model Pengenalan Lapangan Sekolah untuk Menguatkan Kompetensi Calon Guru Biologi di SMA NW Mataram - Nanda Elvi; Siti Hawa (Yayasan Siti Widhatul Faeha, 2025)
This study investigates the implementation of the School Field Introduction Program (FIP) for Biology Education students at the University of Mataram at SMA NW Mataram as part of strengthening their professional competencies. The program aims to integrate theoretical knowledge with authentic calssroom practices. The objective of this study is to describe the stages of PLP I and PLP II, identify challenges encountered during the program, and analyze how the experiential learning framework contributes to students’ pedagogical development. The methods used involved direct observation, participation in school activities, teaching practices sessions, and reflective evaluations involving mentor teachers and supervising lecturers. The results indicate that PLP enhances students’ understanding of school culture, classroom management, and instructional planning, while improving teaching skills through continuous mentoring. However, challenges such as limited facilities and varying student motivation were, required adaptive strategies and varied teaching approaches. The study concludes that PLP significantly supports the development of professional identity and pedagogical readiness in student teachers. The findings highlight the importance of experiential and participatory learning in teacher education and recommend strengthening school–university collaboration to optimize PLP outcomes.